2002
DOI: 10.1212/wnl.58.11.1622
|View full text |Cite
|
Sign up to set email alerts
|

Tau and Aβ42 protein in CSF of patients with frontotemporal degeneration

Abstract: In FTD, CSF levels of tau are elevated and Abeta42 levels are decreased. With use of these markers, subjects with FTD can be distinguished from control subjects and from patients with AD with reasonable accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
117
1
6

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(135 citation statements)
references
References 39 publications
11
117
1
6
Order By: Relevance
“…Results on the performance of these biomarkers for differential diagnosis of FTD and AD have been inconsistent. 30,31,32 However, the pattern of mildly increased tau and moderately decreased Ab 1-42 is not unique for FTD, and it can be assumed that the diagnostic value of these biomarkers to discriminate FTD among dementias other than AD is limited. 33 A disease-specific biomarker test for FTD among dementias other than AD and differential diagnostic non-dementive disorders, such as depressive patients with cognitive complaints, has not yet been established.…”
Section: 524mentioning
confidence: 99%
See 1 more Smart Citation
“…Results on the performance of these biomarkers for differential diagnosis of FTD and AD have been inconsistent. 30,31,32 However, the pattern of mildly increased tau and moderately decreased Ab 1-42 is not unique for FTD, and it can be assumed that the diagnostic value of these biomarkers to discriminate FTD among dementias other than AD is limited. 33 A disease-specific biomarker test for FTD among dementias other than AD and differential diagnostic non-dementive disorders, such as depressive patients with cognitive complaints, has not yet been established.…”
Section: 524mentioning
confidence: 99%
“…This phenomenon has recently contributed to a putative binding protein that masks its epitopes to antibodies during immunologic detection. 4,8,32 Given that similar mechanisms may apply to CSF Ab1-38, the postulated carrier may possess a disease-specific affinity to Ab1-38 in FTD. However, the analogy between the characteristics of the reduction of Ab1-42 and Ab1-38 in AD and FTD, respectively, points to similar diseasespecific mechanisms causing this phenomenon.…”
Section: 524mentioning
confidence: 99%
“…61 The 20 largest studies 14,20,24,41,50,56,[62][63][64][65][66][67][68][69][70][71][72][73][74][75] including more than 2000 AD patients and 1000 controls, evaluating the most commonly used ELISA method for T-tau in CSF, 14 are summarized in Table 2. The mean sensitivity to discriminate AD from nondemented aged individuals has been 81%, at a specificity level of 91% (Table 2).…”
Section: Csf T-taumentioning
confidence: 99%
“…A mild to moderate decrease in CSF A␤42 is found in a percentage of patients with FTD and VAD. 50,52,67,72 …”
Section: A␤42mentioning
confidence: 99%
“…The more recent longitudinal studies use the combination of high tau and low Aβ42 to correlate their levels to the stage of the disease 13,15 . Since amyloid deposition is not exclusive of AD brains, occurring in normal aging and also in other neurological diseases, additional investigation have shown a decrease in Aβ CSF levels in other conditions such as Creutzfeldt-Jakob disease (CJD) 16 , some cases of frontotemporal dementia (FTD) and vascular dementia (VD) 17 . In 1993, Vandermeeren et al 18 developed an immunoassay able to detect tau protein in CSF and subsequent studies concluded that its levels were significantly higher in AD patients when compared to other neurological diseases and normal controls even in the early stages of the disease 4,10 .…”
mentioning
confidence: 99%